2014
DOI: 10.1016/j.exer.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of the lens: An explanation for the zones of discontinuity

Abstract: Keywords: eye lens refractive index zones of discontinuity light scatter implant design a b s t r a c t The structural basis of zones of discontinuity in the living human eye lens has not been elucidated, and there is no conclusive explanation for what relevance they may have to the structure and function of the lens. Newly developed synchrotron radiation based X-ray Talbot interferometry has enabled the detection of subtle fluctuations in the human eye lens which, when used in mathematical modelling to simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…In agreement with our findings, some authors have observed discontinuity zones using a Scheimpflug camera [20]. Castro and associates [21] have recently developed a swept-source optical coherent tomography SS-OCT able to characterize different features in the crystalline lens of older adults with and without a cataract.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, some authors have observed discontinuity zones using a Scheimpflug camera [20]. Castro and associates [21] have recently developed a swept-source optical coherent tomography SS-OCT able to characterize different features in the crystalline lens of older adults with and without a cataract.…”
Section: Discussionsupporting
confidence: 92%
“…If we look at this behaviour in detail, we find that it corresponds with the so called zones of discontinuity. 44,45 These zones are also clearly seen in the first row of the Lens Opacity Classification System (LOCS) chart reproduced in Figure 6. It was found that the additional backscatter at this angle (in addition to the Rayleigh scatter), is spectrally neutral, and rises sharply for more close backward angles.…”
Section: Zones Of Discontinuity or Wasserspaltenmentioning
confidence: 79%
“…This is a mechanical simulation software that can be controlled by parametric design language and is mainly used for Finite Element Analysis. Geometries of models were based on optical measurements of human lenses using X-ray interferometric analysis at the SPring-8 synchrotron [21]. Similar to previous studies [21,22], detailed geometrical parameters used to construct each model were determined by fitting two splines to optical images [21] in SolidWorks (ver.…”
Section: Methodsmentioning
confidence: 99%